How Environmental Leadership Boosts Employees’ Green Innovation Behavior? A Moderated Mediation Model - Xu, Binfeng; Gao, Xiaopei; Cai, Wenjing; Jiang, Lin (Frontiers in Psychology, 2022)
We examined employees’ green organizational identity as a mediator and green organizational climate as a moderator in the relationship between environmental leadership and follower green innovation behavior. Through collecting data (N = 313) from public organizations in China at different times, we found that environmental leadership is positively related to employees’ green innovation behavior through increasing their green organizational identity. Meanwhile, the mediating relationship is conditional on the moderator of green organizational climate. The current study aims to clarify the mechanism and boundary condition in the relationship between environmental leadership and employees’ green innovation behaviors.